Friend or foe : detecting implicit relationships in DBLP - Han, Cindy Bei Bei (2010)
This project can be characterized as an attempt in analyzing and processing the implicit relationships within the Digital Bibliography and Library Project (DBLP) community, particularly those that are resultant of the "publish or perish" pressure omnipresent in academic communities. The DBLP community is an example of those who are not spread from the pressure to keep up or even ahead of their colleagues in the various fields of information sciences and technology. Researchers often collaborate with one another to increase their number of publications as well as exchange knowledge and new concepts. Yet they are also paradoxically challenging one another to bring forth new ideas and technologies that others have not thought of yet.